2006
DOI: 10.1116/1.2395957
|View full text |Cite
|
Sign up to set email alerts
|

Scanning x-ray microscopy investigations into the electron-beam exposure mechanism of hydrogen silsesquioxane resists

Abstract: Electron-beam exposed hydrogen silsesquioxane cross-linking chemistry is investigated by Scanning Transmission X-ray Microscopy (STXM) and Atomic Force Microscopy (AFM). Using STXM, a maximum in the chemical contrast is obtained by measuring the x-ray absorption at 534.5 eV, corresponding to the 1s K-edge transition in oxygen. An area-dependent and dose-dependent chemical conversion is observed for feature sizes between 150 nm and 10 μm and doses between 0.4 mC and 40 mC. The activated (cross-linked) regions e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…Heating of the resist under electron beam exposure was considered negligible ͑i.e., Ͻ1°C͒ taking into account the small e-beam probe size, relatively low beam current and accelerating voltage, thin resist thickness, and good heat conductivity of the Si substrate. This assumption is consistent with data from reports on direct measurement 9 as well as with modeling 10 and analytical evaluation 11,12 of e-beam induced temperature rise. A cascade of Peltier elements was mounted on the stage equipped with an Al heat absorber allowing us to control the temperature of the substrate in range from −20 up to 90°C.…”
Section: Methodssupporting
confidence: 79%
“…Heating of the resist under electron beam exposure was considered negligible ͑i.e., Ͻ1°C͒ taking into account the small e-beam probe size, relatively low beam current and accelerating voltage, thin resist thickness, and good heat conductivity of the Si substrate. This assumption is consistent with data from reports on direct measurement 9 as well as with modeling 10 and analytical evaluation 11,12 of e-beam induced temperature rise. A cascade of Peltier elements was mounted on the stage equipped with an Al heat absorber allowing us to control the temperature of the substrate in range from −20 up to 90°C.…”
Section: Methodssupporting
confidence: 79%
“…Even if a water reaction product was consumed in the reaction via reaction scheme (2), water would be expected to escape at the edges of the reaction front and be detected at higher levels in the EBID. However, because we have observed that exposed, undeveloped films that showed a thickness reduction after exposure 17 would recover their original thickness after a few weeks (suggesting absorption of ambient H 2 O or O 2 by the film), we cannot rule out that reactions (2) and (3) occur after removal from the lithography system.…”
Section: Discussion Of Hsq Reaction Mechanismsmentioning
confidence: 97%
“…In terms of the observed area-dependent exposure dose for HSQ, 15,17 dehydrogenation of silicon may be playing an important role. In radiation exposed polydimethyl silsesquioxane films, hydrogen radicals diffuse considerable distances before reacting.…”
Section: Discussion Of Hsq Reaction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Only a few studies have been published combining DXRL with metallorganic precursors. [17][18][19][20][21][22][23] These previous studies show successful patterning of sol-gel polymethylsisesquioxane-based films but require a buffer coating [17,18] or a crosslink promoter [19] to achieve adequate patterning. In the case of hydrogensilsesquioxanes, sol-gel polymer hybrid films have been patterned using EBL; [21,22] however, these high organic content photoresists present some drawbacks, such as irreproducibility, reaction front propagation beyond the exposed regions, and thermal stability, that need to be overcome.…”
mentioning
confidence: 93%